Implementation of Education Management in Strengthening 'Nyantri Nyunda' Character among Senior High School Students - Solihin; Didi Turmudzi; Azhar Affandi (International Journal of Educational Administration, Management, and Leadership, 2025)
Character education plays a vital role in shaping students' social behavior and national identity in Indonesia's diverse cultural landscape. This study aims to analyze the implementation strategy of the Nyantri Nyunda character education model in Pasundan Senior High Schools in Bandung using an educational management approach. A qualitative descriptive method was employed, involving in-depth interviews, observations, documentation, and focus group discussions with key stakeholders including school principals, teachers, students, and foundation representatives. The findings reveal that while educational management structures are in place, the integration of Nyantri Nyunda values into the curriculum and student behavior remains inconsistent due to gaps in planning, implementation, and evaluation. These values, rooted in Sundanese culture and Islamic teachings, emphasize humility, respect, discipline, and moral integrity—principles essential for holistic student development. However, challenges such as limited teacher competence in value-based education, insufficient parental and community involvement, and inadequate learning resources hinder optimal outcomes. Furthermore, the absence of a standardized framework for integrating local wisdom into school programs contributes to fragmented practices across institutions. Strategic recommendations emphasize the need for participative management that involves all stakeholders in decision-making, continuous professional development for teachers to strengthen their cultural and pedagogical competence, and stronger collaboration between schools, families, and local communities. Enhancing character education through a culturally responsive lens not only strengthens student identity but also reinforces social cohesion and moral citizenship. This study contributes to broader educational discourse by highlighting the potential of local wisdom-based models in promoting character formation aligned with national educational goals.